2004
DOI: 10.1038/sj.ijir.3901270
|View full text |Cite
|
Sign up to set email alerts
|

The effect of overactive bladder syndrome on the sexual quality of life in Korean young and middle aged women

Abstract: Some reports showed that urinary incontinence (UI) or female lower urinary tract symptoms (LUTS) affect life quality and sexual activity. In clinical practice, it is commonly found that not only the symptoms of UI but also overactive bladder (OAB) syndrome affect daily lifestyle and sexual activity, especially in women in the most active era in their social and personal life. However, there is lack of data proving the effect of OAB syndrome on sexual activity or sexual life quality in sexually active age group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 22 publications
(23 reference statements)
5
34
0
4
Order By: Relevance
“…The importance of this relationship is such that combined with the rest of the symptoms and other variables of the patients, it is the only variable that demonstrates to be independently related to the KHQ global score (Table 3). Although the influence of UI symptoms in the sexual function and QoL seems clear, according to different authors [1,10,11], there were no available concluding data on the relative importance of the symptom of urine loss during sexual intercourse on the deterioration of the QoL of women who suffer it. The results of the present study agree with those of the study presented by Oh et al [6] in which women with coital UI showed worse scores in two QoL-measuring questionnaires: the SF-36 Health Survey and the BFLUTS questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of this relationship is such that combined with the rest of the symptoms and other variables of the patients, it is the only variable that demonstrates to be independently related to the KHQ global score (Table 3). Although the influence of UI symptoms in the sexual function and QoL seems clear, according to different authors [1,10,11], there were no available concluding data on the relative importance of the symptom of urine loss during sexual intercourse on the deterioration of the QoL of women who suffer it. The results of the present study agree with those of the study presented by Oh et al [6] in which women with coital UI showed worse scores in two QoL-measuring questionnaires: the SF-36 Health Survey and the BFLUTS questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Kim et al [17] it is found that OAB symptoms could interrupt sexual life 4.8-fold more often than in the asymptomatic group. In another study including an urge incontinence subgroup of OAB, Aslan et al [18] reported that urinary incontinence significantly reduced female sexual function.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, OAB and UUI have been shown to be associated with reduced health-related quality of life (HRQL) and increased rates of depression in women [7][8][9]. Urinary symptoms are also associated with reduced rates of sexual activity and poorer sexual quality of life (QoL) in women [10][11][12][13] and the available data suggest that bladder dysfunction can be a contributor to sexual dysfunction in premenopausal women [14]. Women with UI report impaired sexual function, such as decreased libido, vaginal dryness, and pain during intercourse [15].…”
Section: Introductionmentioning
confidence: 99%